Reinterpreting Performance-Based Budgeting: A Study Of Budgeting Implementation At The Central Sulawesi Provincial Environment Agency - Lasiewa, Wichencha Priskila; Putri , Azzahra Annisa; Usman, Ernawati; Sugianto, Sugianto; Pattawe, Abdul (Jurnal Bisnis, Manajemen dan Akuntansi, 2025)
This research revisits the meaning of performance-based budgeting in public sector organizations, focusing on its implementation at the Environmental Agency Office (DLH) of Central Sulawesi Province. It was conducted qualitatively using an exploratory method through observation, interviews, and theoretical studies. The study results indicate that budget preparation is directed according to the region’s vision and mission and uses Key Performance Indicators to determine program priorities. Transparency and accountability are realized through the publication Center (SRC) as an innovation in converting plastic waste into fuel using pyrolysis technology. Although coordination challenges between fields and the need for system improvement remain, the Environmental Agency of Central Sulawesi Province continues to enhance budget management to support sustainable environmental development.